Actinide endohedral inter-metalloid clusters of the group 15 elements - Zhang, Nai-Xin; Wang, Cong-Zhi; Lan, Jian-Hui; Wu, Qun-Yan; Shi, Wei-Qun (Physical chemistry chemical physics : PCCP, 2024)
Inter-metalloid clusters in Zintl chemistry have been extensively studied due to their unique electronic structures and potential applications. In this work, we explored a series of actinide endohedral inter-metalloid clusters of the group 15 elements [An@Bi 12 ] 4− (An = Th-U) and [An@Sb 12 ] 4− using density functional theory (DFT). [Th@Bi 12 ] 4− and [U@Bi 12 ] 4− exhibit C s symmetry, while [Pa@Bi 12 ] 4− and [An@Sb 12 ] 4− (An = Th-U) have C 1 structures. Bonding analyses such as bond order, molecular orbitals (MO) and quantum theory of atoms in molecules (QTAIM) show covalent An-Bi/An-Sb bonding in the clusters. All these clusters are highly stable according to the studied formation reactions and may be accessible experimentally. Compared with [An@Bi 12 ] 4− , [An@Sb 12 ] 4− possesses stronger bonding interactions, mainly arising from the higher electrostatic interaction energy. For clusters with the same group 15 elements, the bonding interactions increase gradually from Th to U, which is mainly determined by the covalent interactions of An-Bi/An-Sb bonding. This work is expected to provide potential avenues for the construction of robust inter-metalloid clusters of the group 15 elements. Theoretical calculations demonstrate that actinides can stabilize bismuth and antimony cages, forming stable inter-metalloid clusters.